Penerapan Literasi Digital Dalam Meningkatkan Motivasi Dan Prestasi Belajar Siswa Pada Mata Pelajaran Produk Cake Dan Kue Indonesia - Ayu Putu Tristiani; I Ketut Suartana; I Wayan Suryanto (Jayapangus Press, 2023)
The purpose of this study is to know the motivation improvement and students learning achievement through the implementation of digital literacy at XI grade TB 1 SMK Negeri 5, Denpasar on the subject of product Cake and Indonesian Kue. The kind of this study is experiment with quantitave analysis techniques by using method of pre-experimental design type one group pre-test & post-test and purposive sampling techniques. The subject of this study is students at grade XI Tata Boga 1 SMK Negeri 5 Denpasar. On pre-test average value of learning motivation the result showed 112.05, with the highest value is 128.00 and the lowest is 97.00. On learning achievement average value the result showed 68.09, the highest value is 80.00 and the lowest is 56.67. When digital literacy implemented on learning process, on post-test all values improved, namely on learning motivation obtained average value 116.72, the highest value is 130.00 and the lowest is 101.00. On learning achievement showed average value is 80.97, the highest value is 86.33 and the lowest is 78.00. So, it can be concluded that by the implementation of digital literacy maximally on learning process was able to improve students motivation and their learning achievement.